Improved photoelectrochemical hydrogen production over decorated titania with copper and nickel oxides by optimizing the photoanode and reaction characteristics - Bashiri, R. (ELSEVIER SCI LTD, 2020)
We optimized photocatalytic hydrogen production over TiO2-based photocatalyst by varying the dopant (nickel and copper oxide), thin film active area, nature and concentration of sacrificial agents, and light intensity in a photoelectrochemical (PEC) cell/dye-sensitized solar cell (DSSC). Various characterization techniques have been used to investigate the structural, morphological, optical, and PEC behavior of single and codoped TiO2. The TiO2 decorated with both Cu and Ni oxides with active area of 1 cm(2) in a mixture of 5 vol % glycerol and 1 M KOH under light intensity of 100 mWcm(-2) produced the maximum hydrogen of 338.4 mmol cm(-2) for 2 h. The superior photocatalyst performance of this photocatalyst is attributed to its small crystallite size and large pore size, as confirmed by X-ray diffractometer, Transmission electron microscopy (TEM), and surface area of Brunauer-Emmet-Teller (SBET). The absorption edges of this photocatalyst had the highest red shift compared with single doped and pure TiO2 because of more indirect transitions of the photoexcited electrons, greater charge carrier separation, and lower recombination rate. The photoanode active area of 1 cm(2) with better photocatalytic performance correlated with the number of defects and grain boundaries. Glycerol shifted the conduction band of the photocatalyst to more negative flat potential compared with others. Increasing the concentration of glycerol further than 5 vol% saturated the photocatalyst active sites, increased photooxidation intermediates of glycerol, and reduced the hydrogen production. The light intensity had the maximum impact on the hydrogen production and could strongly control the number of charge carriers in both the PEC cell and the DSSC. (C) 2020 Elsevier Ltd. All rights reserved.